Adaptive batching scheme for multicast near video-on-demand (nvod) system - Jain, Madhu; Sharma, Vidushi; Priya, Kriti (Universiti Utara Malaysia, 2006)
Video-on-Demand is becoming most sought after multimedia applications. It is difficult to attain a true video-on-demand (TVOD) system, so near video-on-demand (NVOD) is catching the attention of people. In NVOD, requests are multicast in different streams. Important issue in this system is the choice of batching time. Traditionally the batching time is fixed depending on the number of requests. In this paper we have suggested an adaptive batching scheme (ABS) where batching time is adjusted according to the current arrival rate, which follows the hyper-exponential distribution pattern. A comparison is made between the fixed and adaptive batching schemes. Numerical illustrations are provided to show that adaptive batching policy is better than fixed batching policy for optimizing bandwidth requirements.